The effect of financial inclusion on household consumption expenditure on education - Garcia, Angeli Marie N. (School of Economics, University of the Philippines Diliman, 2018)
There is a growing rate of out_of_school youth in the Philippines and one of the main causes is financial incapability because of limited access to financial services. This paper aims to determine and measure the impact of financial inclusion on educational expenditure of Filipino households using the Consumer Finance Survey 2014. The researchers used ordinary least squares to measure the effect of the covariates to the educational expenditure of households. However, the results were invalid since it did not represent the whole set of observations in the dataset. Thus, to correct for the missing values, the researchers conducted a two_step Heckman model and found out that only formal financial inclusion has a positive effect on educational expenditure. To investigate further, the propensity score matching (PSM) using kernel and radius estimators was also applied and yielded a final result that both formal and informal financial services positively and significantly affects the educational expenditure of the Filipino households. The findings suggest that as people utilize financial services, regardless whether it is formal or informal, households would have increased educational spending that would result in higher productivity, employment, quality of life, and thus, national welfare.